From hands, perfumes and gifts (Journal of Parents and Teachers, 1996)
The article emphasizes the symbolism of hands in creating bonds of trust and affection between people. It also highlights the significance of perfumes and gifts in social interactions. It also mentions the historical and cultural context surrounding these aspects of daily life.
Keywords: hands; trust; gift; social interaction